2001
DOI: 10.1110/ps.ps.24101
|View full text |Cite
|
Sign up to set email alerts
|

The role of strand 1 of the C β‐sheet in the structure and function of α1‐antitrypsin

Abstract: Serpins inhibit cognate serine proteases involved in a number of important processes including blood coagulation and inflammation. Consequently, loss of serpin function or stability results in a number of disease states. Many of the naturally occurring mutations leading to disease are located within strand 1 of the C ␤-sheet of the serpin. To ascertain the structural and functional importance of each residue in this strand, which constitutes the so-called distal hinge of the reactive center loop of the serpin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…We first confirmed thatthe RCL5 loop behavedsimilarlyin our α 1 -PIM358R expression system as previouslyreported (19). Reported ratec onstants for recombinant α 1 -PIM 358R inhibition of thrombin vary,evenbetween laboratoriesemploying bacterial expression (from 6 [38] to 11 [20] to 29 X10 6 M -1 min -1 [32]). Similarly, Hopkinsetal.…”
Section: Discussionsupporting
confidence: 86%
“…We first confirmed thatthe RCL5 loop behavedsimilarlyin our α 1 -PIM358R expression system as previouslyreported (19). Reported ratec onstants for recombinant α 1 -PIM 358R inhibition of thrombin vary,evenbetween laboratoriesemploying bacterial expression (from 6 [38] to 11 [20] to 29 X10 6 M -1 min -1 [32]). Similarly, Hopkinsetal.…”
Section: Discussionsupporting
confidence: 86%
“…We have previously reported that API made in this soluble, intracellular bacterial expression system, exhibits SI values of 2–3 [29] , [30] , [41] . Others employing different bacterial expression systems, some in which recombinant API was renatured from inclusion bodies, have reported SI values closer to unity [55] , [56] . Why the difference arises is not fully understood, but we have demonstrated functionality of API M358R made in this system as an antithrombotic agent in vivo [39] , suggesting that it does not have an unnatural fold.…”
Section: Discussionmentioning
confidence: 96%
“…Changing Glu to Ala probably alters the orientation of the residue side chain away from the solvent towards the body of the protein, which in turn causes loss of stabilizing interactions such as the hydrogen bond. The integrity of β‐sheet C (of which this region is strand 1), is likely to be critical for the correct folding of the serpin in the native metastable state (Eldering et al 1995; Patston and Gettins 1996; Chang et al 1997; Bottomley et al 2001). Another mutant in which we changed the P9′ residue of the α 1 ‐PI‐ LGR Gln to Glu also formed polymers, consistent with this idea (data not shown).…”
Section: Resultsmentioning
confidence: 99%